2014
DOI: 10.1039/c4ta04890c
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous hematite structures to overcome short diffusion lengths in water splitting

Abstract: In this report, we show that by creating a nanoporous haematite (aFe 2 O 3 ) structure using boric acid (H 3 BO 3 ) treatment, the chronic issue of the short diffusion length of carriers in a-Fe 2 O 3 for photo- Photoelectrochemical (PEC) water splitting cells which use solar energy to produce hydrogen or oxygen gas are a promising technology for solving the energy crisis and environmental problems. 1-6 Since Fujishima and Honda rst reported a PEC water splitting system using a titanium dioxide semiconductor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 34 publications
0
55
1
Order By: Relevance
“…Even though, the acid treatment of TNT changes the shape of the nanotube into elliptical granular particles but still provides stronger adhesion on Ti foil. This result indicates that the surface states of the existing TNT is affected in acid treated process, and new structure in TH‐40 might facilitate the short diffusion path to support easy electron transfer in photocatalytic reaction . Figure S1 (A,B) of the Supplementary Information (SI) shows the corresponding FESEM energy dispersive spectrometry (EDS) spectra of the TNT and TH‐40 photoelectrode samples that were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Even though, the acid treatment of TNT changes the shape of the nanotube into elliptical granular particles but still provides stronger adhesion on Ti foil. This result indicates that the surface states of the existing TNT is affected in acid treated process, and new structure in TH‐40 might facilitate the short diffusion path to support easy electron transfer in photocatalytic reaction . Figure S1 (A,B) of the Supplementary Information (SI) shows the corresponding FESEM energy dispersive spectrometry (EDS) spectra of the TNT and TH‐40 photoelectrode samples that were measured.…”
Section: Resultsmentioning
confidence: 99%
“…Although a significant improvement has been made on conductivity of a-Fe 2 O 3 by elemental doping 5,[22][23][24][25] and nanostructuring, [26][27][28][29] the influence of the anodizing process on the photocatalytic performance of a-Fe 2 O 3 photoanode in a PEC cell has not been extensively studied. However, a detailed research on the surface molecular structure of anodized a-Fe 2 O 3 photoanode has been conducted and reported transformation of Fe 21 to Fe 31 states at the surface upon subject to anodizing conditions and the findings were attributed to filling of oxygen vacancies due to increasing oxygen content at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the vertical reciprocating vibration of the single-side cast-rolling roll can promote the dendrite fusing in DOI: 10.1002/crat.201900044 the solidification stage and increase the nucleation rate, thereby refining the crystal grains and increasing the equiaxed grain ratio in the solidified structure. On the other hand, it can apply bidirectional shear force to the high temperature strip to change the stress state of the plastic deformation zone, thereby enhancing the effect of dynamic recrystallization and further refining the crystal grains.…”
Section: Introductionmentioning
confidence: 99%
“…Using hot compression test, Mirzadeh and Parsa studied the thermal deformation and dynamic recrystallization of Ni-Ti metal composites, discussed the influence of Z parameters on critical flow stress, determined the critical stress and strain of initial dynamic recrystallization, and established the constitutive equation of Ni-Ti metal. [10] Bobbili and Madhu studied the dynamic recrystallization of medical alloy Ti-13Nb-13Zr. It was found that the alloy exhibited different microstructures at different temperatures, and its dynamic recrystallization was related to the initial grain size.…”
Section: Introductionmentioning
confidence: 99%